A comprehensive study of the glass/translucent anti-glass/transparent ceramic structural ordering in the Bi2O3Nb2O5–TeO2 system. (1st May 2020) - Dolhen, Morgane; Allix, Mathieu; Sarou-Kanian, Vincent; Fayon, Franck; Genevois, Cécile; Chenu, Sébastien; Coulon, Pierre-Eugène; Colas, Maggy; Cornette, Julie; Duclère, Jean-René; Brisset, François; Masson, Olivier; et al.
Abstract: The full and congruent crystallization of the Bi0.8 Nb0.8 Te2.4 O8 (BNT) glass leads to perfectly transparent ceramic in both the visible and near infrared ranges. While heating the parent glass, an intermediate structural regime order – called anti-glass – that shows chemical inhomogeneity at the nanometer scale and with a long-range cationic ordering while retaining a strong local anionic disorder is observed. Here, we report on the crystallization sequence starting from the Bi0.8 Nb0.8 Te2.4 O8 glass system and show that an intermediate Bi0.8 Nb0.8 Te2.4 O8 anti-glass phase (polymorph 1) is first formed, before transforming into a more ordered and ceramic material (polymorph 2). In particular, we provide a comprehensive structural study of the crossover between glass and its crystalline counterpart through intermediate steps. Similarities and differences between the structures, microstructures of Bi0.8 Nb0.8 Te2.4 O8 glass, anti-glass and ceramic materials of identical composition are investigated in details at different length scales by X-ray and neutron powder diffraction, SEM-EBSD, TEM, NMR and Raman spectroscopy. The optical properties of the anti-glass and ceramic are discussed in correlation with the structure and microstructure observations. This study paves the way for understanding the complex mechanisms at the origin of the full and congruent crystallization from the parent glass. Graphical abstract: Image, graphical abstract